AN ANALYSIS ON MORAL VALUESOF HARRY POTTER AND THE PHILOSOPHERâ€™S STONE NOVEL - Khairunnisa, Khairunnisa; Rufinus, Albert; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe main focus of this research is to find out the moral values of the novel â€œHarry Potter and the Philosopherâ€™s Stoneâ€ by J.K. Rowling based on the major characters. Major characters are the most important actors or people in the novel and they are Harry Potter, Hermione Granger, Ron Weasley, Albus Dumbledore, Hagrid and Professor Snape. One of the key factors that distinguish character from personality is called moral values. Moral values are the things right or wrong in the story which refer to the behavior and the attitude of characters that is giving advices or lessons. The researcher had conducted this research by applying descriptive qualitative method, for describing manner or behavior through quotation of speech or dialogue and action.Â According to the result, there are some moral values found in this novel, they are courage, cleverness, friendly, kindness, patient, politeness, responsibility, self-dicipline, trusworthiness, and wisdom. Those moral values above, can be applied in teaching and learning process, especially for the students in English Education Study Program.Â Keywords: Analysis, Moral values, Novel